2019
DOI: 10.1155/2019/9824728
|View full text |Cite
|
Sign up to set email alerts
|

Yi Guan Jian, a Traditional Chinese Herbal Medicine, Alleviates Carbon Tetrachloride-Induced Liver Injury

Abstract: Objective. To study the protective effect of Yi Guan Jian (YGJ) on liver injury induced by carbon tetrachloride (CCl4) in mice. Methods. 50 ICR mice were randomly divided into 5 groups: control group, carbon tetrachloride (CCl4) group, CCl4 + silymarin Group (200 mg/kg), carbon CCl4 + YGJ Group (11.5, 23 g/kg). Except the mice in the control group and the CCl4 group that were given the same volume of distilled water, the mice in other groups were given the drugs for seven days. 2 hours after the last administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…chloromethane, dichlorocarbene, and trichloromethyl peroxyl radicals. [3][4][5] These radicals can either bind directly to tissues or initiate a cascade of free radical-mediated reactions leading to lipid peroxidation. Therefore, the elevation MDA observed in the CCl4-treated group is a manifestation of CCl4-induced lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…chloromethane, dichlorocarbene, and trichloromethyl peroxyl radicals. [3][4][5] These radicals can either bind directly to tissues or initiate a cascade of free radical-mediated reactions leading to lipid peroxidation. Therefore, the elevation MDA observed in the CCl4-treated group is a manifestation of CCl4-induced lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…YGJ has been widely used in the treatment of chronic liver diseases, including CH, liver fibrosis, and cirrhosis. YGJ has been shown to effectively address chronic liver injury by targeting the MAPK/NF-κB pathway [ 9 ]. It regulates the Wnt signaling pathway to suppress astrocyte activation, thereby mitigating liver fibrosis and impeding cirrhosis progression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies revealed that YGJ not only alleviated clinical symptoms in patients with liver disease but also reduced serum alanine transaminase (ALT) and aspartate transaminase (AST) levels. Although numerous studies have demonstrated the significant role of YGJ in reducing liver inflammation, restoring liver function, and treating CH, the precise mechanism of its action remains unclear [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these ROS are capable of attacking fatty acids and causing peroxidation (Li et al, 2019). As the metabolic endproduct of lipid peroxides, MDA can aggravate cell membrane damage by destroying the function, structure, and metabolism of biofilms (Lixin et al, 2019). SOD is the principal antioxidative enzyme, which can transform free radicals into water and molecular oxygen, thus reducing cell damage (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%